KOMUNITAS MIKROBA PENGAKUMULASI GLIKOGEN - Dyah Supriyati; Rita Dwi Rahayu; Hartati Imamuddin (BERITA BIOLOGI, 2007)
Activated sludge originated from anaerobic-aerobic process waste water treatment plan was acclimated with glucose and acetate.The experiment was conducted in 1 L working volume of sequential batch reactor (SBR) that was adjusted to 0, 25 kg m day.Glucose was effectively utilized by microbial community in anaerobic condition, and glycogen synthesis was occurred in aerobic condition.Suppression of polyphosphate accumulating organism was caused by the domination of glycogen accumulating organism and the high of nitrate production. In order to accelerate the community polyphosphate accumulating organisms then to the competitor of these communities must be pressured.